Evaluation of nineteen food wastes for essential and toxic elements - Saranya Kuppusamy; Kadiyala Venkateswarlu; Mallavarapu Megharaj (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose The study evaluates and provides an overview of the nutritional importance of 19 selected food wastes as aids in human/livestock/soil/plant health. Methods Nitric acid-digested extracts of food wastes belonging to four different classes (fruits, vegetables, oilseeds and beverages) were analysed for different elements in an inductively coupled plasma mass spectrometer. Results Our study recommends spent coffee grounds, tea leaves, radish peel, watermelon rind and pineapple skin that contain substantially high concentrations of essential elements such as N, P, K, S and Fe for their use as: (a) substrates for composting, (b) biofertilizers, (c) soil amendments, and (d) bioadsorbents of toxins. Although these food wastes are rich in essential nutrients, we do not suggest them for the preparation of food supplements as they contain non-essential elements in concentrations beyond the human safety limits. However, food wastes like banana peel, plum pomace and pistachio shell that contain low and permissible concentrations of toxic elements can be recommended as dietary supplements for oral intake in spite of their lesser essential elemental composition than the other residues examined. Conclusions Our study confirms that food wastes are rich sources of essential nutrients and there is need to harness their real industrial systems.